Who can best report on children's motor competence: Parents, teachers, or the children themselves?. (January 2018) - Estevan, Isaac; Molina-García, Javier; Bowe, Steven J.; Álvarez, Octavio; Castillo, Isabel; Barnett, Lisa M.
Abstract: Objective: A positive perception of motor competence (MC) is important for children's health trajectory. It is purported that young children's perception is not well aligned with their actual ability. Alternative sources of perceptions are postulated from children's social context such as their parents or teachers. This study aims to analyse the associations among children's, parents' and Physical Education (PE) teachers' perception of children's MC and the children's actual MC, and whether these sources of information can report on children's actual MC. Design and method: A convenience sample of 139 typically developed children (48.2% girls) from six schools participated in this cross-sectional study. Actual and perceived MC was assessed by using the Test of Gross Motor Development and the Perceived Movement Skill Competence scale, respectively. Spearman's rho correlation and multilevel mixed-effects linear regression models were conducted. Results: Weak, weak-moderate and moderate positive associations were found between children's, parents' and PE teachers' reports and children's MC ( p < 0.05), respectively. Children presented limited capability in explaining their actual MC. Parents' and PE teachers' proxy reports on children' MC were predictors of children's MC, with PE teachers best able to report on children's MC. Conclusion: Taking into account the resources needed to objectively assess children's actual MC, this study offers alternative sources of information for educators, researchers and/or therapists to assist in reporting children's actual MC. Highlights: Specific and aligned instruments to study perceived and actual MC should be used. Children seem to present limited ability to report their MC. Parents' and PE Teachers' proxy reports can be seen as good sources of information.